How can latent trajectories of back pain be translated into defined subgroups? - Kongsted, A.; Hestbæk, L.; Kent, Peter (Biomed Central Ltd, 2017)
Background: Similar types of trajectory patterns have been identified by Latent Class Analyses (LCA) across multiple low back pain (LBP) cohorts, but these patterns are impractical to apply to new cohorts or individual patients. It would be useful to be able to identify trajectory subgroups from descriptive definitions, as a way to apply the same definitions of mutually exclusive subgroups across populations. In this study, we investigated if the course trajectories of two LBP cohorts fitted with previously suggested trajectory subgroup definitions, how distinctly different these subgroups were, and if the subgroup definitions matched with LCA-derived patterns. Methods: Weekly measures of LBP intensity and frequency during 1 year were available from two clinical cohorts. We applied definitions of 16 possible trajectory subgroups to these observations and calculated the prevalence of the subgroups. The probability of belonging to each of eight LCA-derived patterns was determined within each subgroup. LBP intensity and frequency were described within subgroups and the subgroups of 'fluctuating' and 'episodic' LBP were compared on clinical characteristics. Results: All of 1077 observed trajectories fitted with the defined subgroups. 'Severe episodic LBP' was the most frequent pattern in both cohorts and 'ongoing LBP' was almost non-existing. There was a clear relationship between the defined trajectory subgroups and LCA-derived trajectory patterns, as in most subgroups, all patients had high probabilities of belonging to only one or two of the LCA patterns. The characteristics of the six defined subgroups with minor LBP were very similar. 'Fluctuating LBP' subgroups were significantly more distressed, had more intense leg pain, higher levels of activity limitation, and more negative expectations about future LBP than 'episodic LBP' subgroups. Conclusion: Previously suggested definitions of LBP trajectory subgroups could be readily applied to patients' observed data resulting in subgroups that matched well with LCA-derived trajectory patterns. We suggest that the number of trajectory subgroups can be reduced by merging some subgroups with minor LBP. Stable levels of LBP were almost not observed and we suggest that minor fluctuations in pain intensity might be conceptualised as 'ongoing LBP'. Lastly, we found clear support for distinguishing between fluctuating and episodic LBP.